PERAN DISIPLIN MASYARAKAT DALAM MENJAGA BUDAYA HIDUP BERSIH TERHADAP LINGKUNGAN (Suatu Studi di Desa Tuabatu Kecamatan Tampan Amma Kabupaten Talaud) - Bara, Deismon; Lasut, Jouke J.; Goni, Shirley Y. V. I. (HOLISTIK, Journal Of Social and Culture, 2018)
Creates an environment comfortable, orderly, clean and also in accordance with rules and regulation in the community needs to be an awareness and care any member of the peoples of the situation and the condition the environment around them because of the landscape is a man to run various activity and the interaction with another.One of phenomenon interesting that the care and public awareness Tuabatu of environment cleanliness is weak. Even though the government had worked counselor, coaching and briefing about awareness and concern for the environment around them.Clean environment is imaging all of, but is not easy to create environments our look clean and tidy so that would be comfortable seen. Often because bustle and various another reason, so that we less aware of cleanliness of the environment in around us.Tuabatu village there were a habit people who throw garbage in public places this is very relating to the level of public awareness. The habit is very difficult to overcome that it deals with a tradition. If the traditions of a society changed so custom would turn hence tradition and habits are related in creating a clean and healthy environment.Keywords: environment, helth, awareness